A novel control strategy for effects of Right-Half Plane Zero in three-phase voltage source rectifier - Chuyang Wang; Li Zhang; Zitao Zhang (Energy Reports, 2022)
The linear model of the three-phase voltage source rectifier (VSR) proposed before could not provide an accurate description for the stability and dynamics performance when the output power is high, the inductances are large or the boost ratio is high. Hence, an item of Right-Half Plane Zero (RHPZ), which contains the output power, the inductances and the boost ratio, is introduced into the linear model in this paper, where its derivation and physical interpretation are also provided. After the introduction, the quantitative analysis for the RHPZ effects, including the decrease of the stability, the deterioration of the dynamic performance and the overshoot of the DC-link voltage, are provided in this paper. According to the analysis, a novel control strategy is proposed to enhance the stability to improve the dynamic performance and to restrain the voltage overshoot. Finally, simulation and experimental results verify that this control strategy has a great validity to reduce the RHPZ effects.